2011
DOI: 10.15193/zntj/2011/79/177-191
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Edible Protein-Wax Coating on Post-Harvest Stability of Brussels Sprouts Stored Under Simulated Commercial Storage Conditions

Abstract:  WPŁYW JADALNEJ POWŁOKI BIAŁKOWO-WOSKOWEJ NA TRWAŁOŚĆ POZBIORCZĄ KAPUSTY BRUKSELSKIEJ PRZECHOWYWANEJ W SYMULOWANYCH WARUNKACH OBROTU TOWAROWEGOS t r e s z c z e n i e Umyte główki kapusty brukselskiej poddano powlekaniu poprzez zanurzenie w powłoce, którą stanowił wodny roztwór białka grochu (10 % m/m), wosku kandelila (2 % m/m) i sorbitolu (4 % m/m). Powlekane oraz niepowlekane (próba kontrolna) warzywa przechowywano przez 10 dni w symulowanych warunkach obrotu towarowego (~20 ºC, wilgotność względna powietr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 27 publications
2
2
2
Order By: Relevance
“…Both control and coated Brussels sprouts kept their initial firm texture (~11.85 N) through the whole storage period (Table ). Contrary to previous study (Kowalczyk, ), the coating treatment did not affect the hardness of vegetables ( p > 0.05). This inconsistency may be explained by differences in the storage conditions, including the packaging application.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…Both control and coated Brussels sprouts kept their initial firm texture (~11.85 N) through the whole storage period (Table ). Contrary to previous study (Kowalczyk, ), the coating treatment did not affect the hardness of vegetables ( p > 0.05). This inconsistency may be explained by differences in the storage conditions, including the packaging application.…”
Section: Resultscontrasting
confidence: 99%
“…It was found that the coating treatment increased chlorophyll degradation in the vegetables (Table ). This is in agreement with the results of earlier study (Kowalczyk, ). A possible explanation for this might be that the gas barrier properties of the coating caused accumulation of ethylene in the internal atmosphere of vegetable tissues.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations